The new world of southeast Asia - Mills, Lennox A. (Lennox Algernon), 1896-1968 (University of Minnesota Press, 1949)
The New World of Southeast Asia was first published in 1949. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.